Raman Spectroscopy Principles for in vivo Diagnostic by Ellipsoidal Reflectors - Bezuglyi Mikhail; Bezuglaya Natalia (Electrical, Control and Communication Engineering)
The paper presents the analysis of the functional abilities of measurement tools with ellipsoidal reflectors for Raman spectroscopy. The investigated structural scheme of the setup is intended for use in Raman spectroscopy in vivo by ellipsoidal reflectors. The setup can be used as a prototype for development of a device for non-invasive control of sugar level. Additionally, the investigation demonstrates the efficiency of ellipsoidal photometry method for registration of Raman scattering signal on test-solutions. The testing was performed for different sugar concentrations with the laser radiation wavelength 980 nm. In addition, the selecting principles of laser radiation source parameters (including beam diameter and power) were investigated. During the research, the data about spatial distribution of the backscattered light in human shoulder and finger tissues during photometry by ellipsoidal reflectors were received. The procedure involves application of Monte Carlo simulation. The dependency of the external and middle ring illuminance of photometric images on the diameter and power of the laser beam is represented based on the zone analysis.